Gema Perdamaian: Tourism, Religion and Peace in Multicultural Bali - Shinji Yamashita, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Balinese tourism has experienced serious challenges because of such negative incidents as the bombings by the Muslim terrorists in the Balinese resort of Kuta in 2002 and 2005. The inter-faith measures enacted as part of the crisis management for Balinese tourism after the bombings on 12 October 2002 are particularly interesting. These measures included joint- prayers to promote interreligious harmony such as the prayer for world peace, Doa Perdamainan Dunia dari Bali (“Prayer for Peace of the World from Bali”) on 21 October 2002, which was attended by the minister of religious affairs, who is himself Muslim. In this event the bombings were then interpreted by Balinese as an expression of the anger of gods, a consequence of bad karma. Therefore, a massive ceremony, involving the most powerful priests, was carried out on 15 November 2002 in order to cleanse Bali of the trauma of the bombing and restore peace. Since then the “prayer for peace” (Gema Perdamaian, literally “Echo of Peace”) has continued to be held on 12 October every year. By focusing on this event and the Balinese peace movement after the bombings, this paper discusses a new relationship between tourism, religion and peace within the framework of multicultural Bali in the age of transnationalism
Keywords: Gema Perdamaian; tourism; religion; peace; multiculturalism; transnationalism